Can climate-resilient agriculture become an engine for Syria’s post-conflict recovery? - Schapendonk, Frans; Rabie, Sara (2025)
Syria finds itself at a crossroads. Faced with the imminent need to prevent a relapse into renewed short-term insecurity, its government also must start to develop longer-term strategies to support recovery. Generating peace dividends for Syria’s embattled population requires confronting the ecological threats which currently undermine basic human security across the country. Nowhere do these threats emerge more prominently than in its agricultural sector. Ensuring that this essential sector lives up to its potential as an engine for economic stabilization and peace will require a set of targeted – and climate-sensitive – investments and interventions.